Driving Individual Taxpayer Compliance: How Information Technology Elevates Tax Service Quality, Social Engagement and Education - Edi Triwibowo; Dian Sulistyorini Wulandari; Titi Nandarwati (Journal of Scientific Interdisciplinary, 2024)
This study investigates the factors influencing Individual Taxpayer Compliance in Indonesia, focusing on Tax Service Quality, Social Engagement and Education, and the moderating role of Information Technology. The findings reveal that Tax Service Quality does not significantly impact taxpayer compliance, suggesting that improvements in service quality alone may not suffice to enhance compliance levels. In contrast, Social Engagement and Education are significant factors that positively influence taxpayer compliance, indicating the effectiveness of educational initiatives and community involvement in fostering compliance behavior. Furthermore, information technology has been found to have no significant moderating effect on the relationship between tax service quality or social engagement, education, or taxpayer compliance. These results underscore the importance of prioritizing social engagement and educational strategies while recognizing that technology should be integrated as a complementary tool to improve compliance outcomes. A balanced approach combining these elements is essential for fostering a more compliant taxpayer environment in Indonesia.